Intraluminal Monitoring of Micro Vessels. A Surgical Feasibility Study - Walle, Leonard; Sudhoff, Holger; Frerichs, Onno; Todt, Ingo (Frontiers in Surgery, 2021)
Objective: Monitoring of vessel perfusion is of high clinical importance in vascular anastomosis of free flaps. Current sensor systems are based on different principles and show limitations in validity and accuracy. Fiber optic pressure sensors exhibit high accuracy and are small in size. The aim of the present study was to evaluate the surgical feasibility of intraluminal pressure (ILP) measurements with a fiber optic pressure sensor in an animal model. Methods: We introduced a 600 µm fiber optic pressure sensor into the A. carotis communis of 10 and V. jugularis of 10 rats and measured the ILP in a microsurgery setting. The sensor was stabilized by the surrounding tissue, and the vessels were closed. Results: In all cases, surgical placement was uneventful. Measurement of intra-venous and intra-arterial pressure was possible and stable over the whole measurement period of an hour. Conclusion: Fiber optic pressure measurement in microvessels is possible and surgically feasible. An application to monitor the perfusion of free flaps seems possible.